Amino acids in cancer - Lieu, Elizabeth L.; Nguyen, Tu; Rhyne, Shawn; Kim, Jiyeon (Experimental & molecular medicine, 2020)
Over 90 years ago, Otto Warburg’s seminal discovery of aerobic glycolysis established metabolic reprogramming as one of the first distinguishing characteristics of cancer 1 . The field of cancer metabolism subsequently revealed additional metabolic alterations in cancer by focusing on central carbon metabolism, including the citric acid cycle and pentose phosphate pathway. Recent reports have, however, uncovered substantial non-carbon metabolism contributions to cancer cell viability and growth. Amino acids, nutrients vital to the survival of all cell types, experience reprogrammed metabolism in cancer. This review outlines the diverse roles of amino acids within the tumor and in the tumor microenvironment. Beyond their role in biosynthesis, they serve as energy sources and help maintain redox balance. In addition, amino acid derivatives contribute to epigenetic regulation and immune responses linked to tumorigenesis and metastasis. Furthermore, in discussing the transporters and transaminases that mediate amino acid uptake and synthesis, we identify potential metabolic liabilities as targets for therapeutic intervention. Cancer: How tumors hijack basic building blocks Cancer changes how the body uses amino acids, the building blocks that all proteins are made of. A better understanding of these changes could lead to new cancer therapies. Cancer was already known to alter the body’s sugar metabolism to feed extra energy to fast-growing tumors. Recent reports have revealed that cancer also rewires amino acid metabolism. Jiyeon Kim at the University of Illinois at Chicago, USA, and co-workers have reviewed how cancer co-opts amino acids. They report that tumors use amino acids as an energy source and antioxidant precursor to balance their production of toxic reactive oxygen species. Amino acids are also instrumental in annotating the epigenetic code to enhance or suppress expression of tumor-related genes. The review illuminates a promising new approach to cancer therapeutics.